# Solve for y 5(2y-1)=2(2+3y)

5(2y-1)=2(2+3y)
Simplify 5(2y-1).
Apply the distributive property.
5(2y)+5⋅-1=2(2+3y)
Multiply.
Multiply 2 by 5.
10y+5⋅-1=2(2+3y)
Multiply 5 by -1.
10y-5=2(2+3y)
10y-5=2(2+3y)
10y-5=2(2+3y)
Simplify 2(2+3y).
Apply the distributive property.
10y-5=2⋅2+2(3y)
Multiply.
Multiply 2 by 2.
10y-5=4+2(3y)
Multiply 3 by 2.
10y-5=4+6y
10y-5=4+6y
10y-5=4+6y
Move all terms containing y to the left side of the equation.
Subtract 6y from both sides of the equation.
10y-5-6y=4
Subtract 6y from 10y.
4y-5=4
4y-5=4
Move all terms not containing y to the right side of the equation.
Add 5 to both sides of the equation.
4y=4+5
4y=9
4y=9
Divide each term by 4 and simplify.
Divide each term in 4y=9 by 4.
4y4=94
Cancel the common factor of 4.
Cancel the common factor.
4y4=94
Divide y by 1.
y=94
y=94
y=94
The result can be shown in multiple forms.
Exact Form:
y=94
Decimal Form:
y=2.25
Mixed Number Form:
y=214
Solve for y 5(2y-1)=2(2+3y)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top